Effects of Steam and Alkali Treatment on Chemical Composition and in vitro Digestibility of Oil Palm Trunks - Ab. Raman, Ismail; Oshio, S.; Khoo, Kean Choon (1990)
Oil palm trunks (OPT)were sawn into planks,reduced to flakes and processed for use in feeding trials to bulls. The optimum size of flakes was found to be 2cm with three different treatment for drying , streaming and alkali treatments.Chemical analysis and in vitro dry matter digestibility were determined on materials. Steam treatment decreased the neutral detergent fiber ( NDF) but did not cause considerable change in the acid detergent fiber ( ADF)content. The acid detergent lignin (ADL ) content was increased . The optimum dry matter digestibilities at steam pressures of 7. 5, 10.0, 12.5 were obtained at steaming times of 60 , 20. 10 and 5min respectively. Treatment with sodium hydroxide also decreased the NDF content.The ADF content was only lowered at concentrations of NaOH greater than 6%. The ADL content was increased due to removal of carbohydrates.Disruption of the lignin-polysaccharide bonds led to a rise in the in vitro dry matter digestibility .The optimum digestibility was obtained by treatment with 9% NaOH 14 days.